Letter from Hope Mendoza Schechter - Hope Mendoza Schechter:::::: (1969)
In this April 21, 1969 letter, the Democratic Women's Forum expresses outrage over the verbal abuse and disruption directed at Democratic National Committeewoman Carmen Warschaw during an April 11 meeting in Sacramento, arguing that such behavior violates principles of free speech and democratic discourse. The Forum is particularly disturbed not only by the harassment but also by the failure of party leadership to intervene and uphold standards of fair play. Citing similar incidents involving Hubert Humphrey, James Reston, and Wayne Morse, the letter warns of a growing pattern of anti-democratic disruption and urges leaders to take action to protect open debate.